Physical Characteristics of Arctic Fox (Alopex lagopus) Dens in Northern Yukon Territory, Canada - Smits, C.M.M.; Smith, C.A.S.; Slough, B.G. (ARCTIC, 1988)
Physical characteristics of arctic fox (Alopex lagopus) dens on Herschel Island and the Yukon Coastal Plain, Yukon Territory, Canada, are described. The preferred den habitat on Herschel Island is characterized by moderately eroded, sloping, gullied terrain, where foxes select sandy erosional mounds for denning. The preferred habitat on the Yukon Coastal Plain is fluvial landforms, where foxes select streamside cutbanks and occasional dunes for den location. Dens are generally associated with relatively warm, well-drained landscape positions. Burrow entrances are significantly oriented toward the south (P<0.0025). Soils of dens are coarse textured, typically sandy loam to sand. Depth to permafrost is significantly greater under the den than at adjacent sites (p<0.02). Certain unique soil profile characteristics, particularly the replacement of common cryoturbation (frost churning) features with those zooturbation (faunal mixing) and the formation of humus-rich surface horizons, appear to be the result of denning activities by foxes. Observed differences in soil temperature and depth to permafrost between den site soils and adjacent soils have likely been caused, at least in part, by denning activities.Key words: arctic fox (Alopex lagopus), dens, soil characteristics, habitat, distribution, northern Yukon Territory Mots clés: renard polaire (Alopex lagopus), renardières, caractéristiques du sol, habitat, distribution, nord du Yukon